Pengaruh Ekonomi Makro Terhadap Indeks Harga Saham Gabungan Tahun 2017 - 2021 - Wibisono, Hermawan; Indah, Novi Permata (Peneliti.net, 2023)
The capital market macroeconomics plays an important role in the country's economy, one of which is to obtain sources of funds and optimize the allocation of economic resources. An investor must have the ability to understand capital market conditions in the future when making an investment decision. there are several factors that can affect stock movements such as inflation, interest rates, world oil prices, GDP. The method used in this study is a descriptive verification method and uses a quantitative approach. The aim is to provide clarity to research with the support of data analysis and literature studies in the form of figures that have been collected. Inflation, the BI Rate and GDP do not partially affect the JCI while world oil prices partially affect the JCI. the variable inflation, BI Rate, World Oil Prices and GDP have an effect on the dependent variable, namely the JCI of 65.1%. While the remaining 34.9% is influenced by other factors not examined. The Indonesian government should make more efforts to control macroeconomic events that have a significant role and impact on the Indonesian economy, so as to attract investors to invest in the capital market.